The Srebrenica exhibition - Dion van den Berg; Martin J.M. Hoondert (Oñati Socio-Legal Series)
In February 2017, an exhibition was opened in Srebrenica (Bosnia and Herzegovina) telling the story of the Bosnian war (1992-1995) and the Srebrenica genocide (1995). In this article we describe how the exhibition was designed and we reflect on the impact of the exhibition on the processes of restorative justice and social reconstruction. Leading question is: Does the exhibition successfully construct a shared sense of truth about the Srebrenica genocide? This evaluative question demands insight in the concept of truth and, more specific, in the debate about plural truths and multiple narratives.